Effects after inhalation of (1 → 3)-β-D-glucan and relation to mould exposure in the home - Lena Beijer; Jörgen Thorn; Ragnar Rylander (Mediators of Inflammation)
Background: Damp conditions indoors favour the growth of microorganisms, and these contain several agents that may cause inflammation when inhaled. Moulds contain a polyglucose in their cell wall, defined as (1→3)-β-D-glucan, exhibiting effects on inflammatory cells.